Analisis jejaring sosial gempa Cianjur di Twitter sebagai mitigasi dampak bencana - Gema Nusantara Bakry (Faculty of Communications Science, Dr. Soetomo University, 2023)
Indonesia is a country that has the potential for volcanic and tectonic earthquakes. One of the actions that can be taken to minimise the impact of disasters is to mitigate natural disasters through social media, such as Twitter. The #PrayForCianjur hashtag is one of the efforts to expand information by utilising Twitter to minimise the impact of the disaster in Cianjur as well as provide prompt action from related parties. This research aims to analyse the social network hashtag #PrayForCianjur, which became a topic of public discourse on Twitter after the Cianjur earthquake occurred. The study results show that the information centre actors are non-institutional actors such as @marchfoward, @aqfiazfan, @tanyakanrl, and @convomf. Meanwhile, institutional actors such as @nctzenhumanity, @detik.com, and @info_bmkg There are interesting findings in this research: actors who should be actively involved in disaster mitigation are not popular in the network. This study will operate as a foundation for providing the crisis management and mitigation teams with helpful information that they can use to prepare for and plan an efficient disaster response and to support the creation of automated crisis management systems in the future.